FINAL STAGES OF MAGMA EVOLUTION IN KLYUCHEVSKOY VOLCANO, KAMCHATKA: EVIDENCE FROM MELT INCLUSIONS IN MINERALS OF HIGH-ALUMINA BASALTS - Mironov N.L.; Pletchov P.Yu.; Portnyagin M.V.; Khubunaya S.A. (My University, 2001)
Magmatic inclusions were studied in phenocrysts from the high-alumina basalts of Klyuchevskoy Volcano, with special emphasis on melt inclusions in olivine (Fo 71-79), clinopyroxene (Mg# = 70-81), and plagioclase (An 47-84) phenocrysts. Glassy melt inclusions were analyzed for major elements by an electron microprobe, and water content was estimated by various calculation methods. The data obtained allowed us to estimate the physicochemical conditions of melt crystallization. Variation in water content was the major factor controlling liquidus phase relationships of the melts. Water accumulation during olivine and clinopyroxene crystallization resulted in delay of plagioclase crystallization and melt enrichment in Al 2O 3 producing magmas chemically similar to high-alumina basalt. The subsequent evolution of melt composition was controlled by plagioclase crystallization from the magma, which resulted in melt depletion in Al 2O 3. The phenocrysts of olivine (Fo 71-79), clinopyroxene (Mg# = 70-81), and plagioclase (An 41-84) of high-alumina basalts crystallized from compositionally diverse melts at temperatures 1145-1030°C and pressures no higher than 3.0-3.5 kbar (1.5 kbar, on the average). The earliest of these phenocrysts correspond to melts containing ∼5-6 wt % MgO and varying amounts of Al 2O 3 (16-20 wt %) and H 2O (0-5 wt %). A model is proposed for the final stage of the Klyuchevskoy Volcano magma evolution. According to this model, the crystallization of minerals of the high-alumina basalts occurred under conditions of rapid decompression during magma ascent toward the surface and was accompanied by a decrease in H 2O content owing to degassing of the magma. It was shown that the formation of dacite melt trapped by the plagioclase and clinopyroxene phenocrysts was probably related to the processes of extensive crystal fractionation of initial basaltic magmas. The formation of more silicic melts can be explained by the specific mechanism of melt inclusion entrapment by plagioclase crystals.